Body condition and corticosterone stress response, as markers to investigate effects of human activities on Adélie penguins (Pygoscelis adeliae) - Marciau, Coline; Raclot, Thierry; Bestley, Sophie; Barbraud, Christophe; Delord, Karine; Hindell, Mark Andrew; Kato, Akiko; Parenteau, Charline; Poupart, Timothée; Ribout, Cécile; Ropert-Coudert, Yan; Angelier, Frédéric (Frontiers in Ecology and Evolution, 2023)
In Antarctica, there is growing concern about the potential effect of anthropogenic activities (i.e., tourism, research) on wildlife, especially since human activities are developing at an unprecedented rate. Although guidelines exist to mitigate negative impacts, fundamental data are currently lacking to reliably assess impacts. Physiological tools, such as circulating corticosterone levels, appear promising to assess the potential impact of human disturbance on Antarctic vertebrates. In this study, we compared the body condition, and the physiological sensitivity to stress (i.e., basal and stress-induced corticosterone level) of adult and chick Adélie penguins between a disturbed and an undisturbed area (i.e., 2 colonies located in the middle of a research station exposed to intense human activities and 2 colonies located on protected islands with minimal human disturbance). We did not find any significant impact of human activities on body condition and corticosterone levels in adults (incubating adults, brooding adults). In chicks, there were significant inter-colony variations in stress-induced corticosterone levels. Specifically, the chicks from the disturbed colonies tended to have higher stress-induced corticosterone levels than the chicks from the protected areas although this difference between areas was not significant. Overall, our study suggests that this species is not dramatically impacted by human activities, at least when humans and penguins have cohabited for several decades. Our results support therefore the idea that this species is likely to be tolerant to human disturbance and this corroborates with the persistence of Adélie penguin colonies in the middle of the research station. However, our results also suggest that chicks might be more sensitive to human disturbance than adults and might therefore potentially suffer from human disturbance. In addition, and independently of human disturbance we also found significant differences in adult body condition, and chick corticosterone level between colonies, suggesting that other individual and environmental variables outweigh the potential minor impact of human disturbance on these variables. Combining corticosterone with complementary stress-related physiological markers, such as heart rate, may strengthen further studies examining whether human disturbance may have subtle detrimental impacts on individuals.